Salinomycin efficiency assessment in non-tumor (HB4a) and tumor (MCF-7) human breast cells - Niwa, Andressa Megumi; Rocha D'Epiro, Glaucia Fernanda; Marques, Lilian Areal; Semprebon, Simone Cristine; Sartori, Daniele; Ribeiro, Lucia Regina [UNESP]; Mantovani, Mario Sergio (Springer, 2016)
The search for anticancer drugs has led researchers to study salinomycin, an ionophore antibiotic that selectively destroys cancer stem cells. In this study, salinomycin was assessed in two human cell lines, a breast adenocarcinoma (MCF-7) and a non-tumor breast cell line (HB4a), to verify its selective action against tumor cells. Real-time assessment of cell proliferation showed that HB4a cells are more resistant to salinomycin than MCF-7 tumor cell line, and these data were confirmed in a cytotoxicity assay. The half maximal inhibitory concentration (IC50) values show the increased sensitivity of MCF-7 cells to salinomycin. In the comet assay, only MCF-7 cells showed the induction of DNA damage. Flow cytometric analysis showed that cell death by apoptosis/necrosis was only induced in the MCF-7 cells. The increased expression of GADD45A and CDKN1A genes was observed in all cell lines. Decreased expression of CCNA2 and CCNB1 genes occurred only in tumor cells, suggesting G2/M cell cycle arrest. Consequently, cell death was activated in tumor cells through strong inhibition of the antiapoptotic genes BCL-2, BCL-XL, and BIRC5 genes in MCF-7 cells. These data demonstrate the selectivity of salinomycin in killing human mammary tumor cells. The cell death observed only in MCF-7 tumor cells was confirmed by gene expression analysis, where there was downregulation of antiapoptotic genes. These data contribute to clarifying the mechanism of action of salinomycin as a promising antitumor drug and, for the first time, we observed the higher resistance of HB4a non-tumor breast cells to salinomycin.
Keywords: Salinomycin; Cancer; Cytotoxicity; Genotoxicity; Apoptosis